2018
DOI: 10.1183/13993003.02509-2017
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for lung disease progression in children with cystic fibrosis

Abstract: To identify potential risk factors for lung disease progression in children with cystic fibrosis (CF), we studied the longitudinal data of all children with CF (aged ≥5 years) registered in the Dutch CF Registry (2009-2014).Lung disease progression was expressed as a decline in lung function (forced expiratory volume in 1 s (FEV) % pred) and pulmonary exacerbation rate. Potential risk factors at baseline included sex, age, best FEV % pred, best forced vital capacity % pred, genotype, body mass index z-score, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 34 publications
2
10
0
Order By: Relevance
“…A recent global survey of patients, carers and clinicians has indicated that "relieving gastrointestinal symptoms" and "simplifying treatment" were in the top three of 10 consensus research priorities identified in CF [6]. We therefore agree with the view expressed by VAN HORCK et al [1], that the association between PPI use and lung disease progression in CF requires investigation. We feel that such "aerodigestive" studies may be relevant for other chronic lung diseases where reflux has been implicated [7] and where PPI treatment is common.…”
Section: Risk Factors For Lung Disease Progression In Children With Csupporting
confidence: 77%
See 2 more Smart Citations
“…A recent global survey of patients, carers and clinicians has indicated that "relieving gastrointestinal symptoms" and "simplifying treatment" were in the top three of 10 consensus research priorities identified in CF [6]. We therefore agree with the view expressed by VAN HORCK et al [1], that the association between PPI use and lung disease progression in CF requires investigation. We feel that such "aerodigestive" studies may be relevant for other chronic lung diseases where reflux has been implicated [7] and where PPI treatment is common.…”
Section: Risk Factors For Lung Disease Progression In Children With Csupporting
confidence: 77%
“…We also documented symptoms of extra-oesophageal, gastroduodenal reflux, a known precursor to aspiration. This indicates the possibility of gut to lung movement of micro-organisms, considered by VAN HORCK et al [1], and a potential mechanism long-recognised in lung disease. Micro-aspiration and potential gut to lung microbial movement has also been shown in radiolabel studies of normal subjects [3,4].…”
Section: Risk Factors For Lung Disease Progression In Children With Cmentioning
confidence: 72%
See 1 more Smart Citation
“…In a recent retrospective study of 114 adults with CF, PPI use was associated with a higher prevalence of clinically-diagnosed GER and a higher mean number of hospitalizations for pulmonary exacerbations in both univariate and multivariate models; there was no difference in Pa colonization between those on PPI and those who were not 18 . In a Dutch CF registry study of patients aged 5–18 years, use of PPI was associated with an accelerated annual decline in FEV1% predicted (estimated pooled effect −0.69, 95% CI −1.26- −0.12) as well as increased risk of pulmonary exacerbations, adjusted for Pa colonization and other risk factors 19 . Another single site retrospective chart review of 126 CF patients on PPI for ≥ 6 months showed higher rates of at least one pulmonary exacerbation (59.6%) compared to only 24.5% of the 49 CF patients not on PPI 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Use of proton pump inhibitors was found to be a significant risk factor for decline in FEV1pp and pulmonary exacerbations in a study of the Dutch CF Registry. In addition, a longer duration of PPI therapy led to a faster rate of FEV1pp decline …”
Section: Infection Detection and Epidemiologymentioning
confidence: 99%